Pelatihan Kewirausahaan bagi Wirausaha Pemuda Karang Taruna dan PKK Desa Kaladawa, Kecamatan Talang, Kabupaten Tegal - M.Masrukhan (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Entrepreneurship training is an important strategy in the economic empowerment of village communities, especially for the youth of Karang Taruna and PKK members who have a strategic role in local development. In Kaladawa Village, local potentials such as agricultural products, processed food, and handicrafts actually have a fairly high economic value. However, this potential has not been utilized optimally due to low knowledge, skills, and access to information and technology that supports entrepreneurship. Lack of understanding of business planning, digital marketing, and financial management is often the main obstacle that hinders village communities from starting and developing businesses independently. This community service activity aims to increase the capacity and economic independence of the residents of Kaladawa Village through practice-based entrepreneurship training. The training is comprehensively arranged, combining interactive lecture methods, group discussions, case studies, and simple business simulations so that participants are able to understand in theory and practice. The training material includes basic concepts of entrepreneurship, identification and analysis of local potential-based business opportunities, preparation of business plans, digital marketing strategies using social media, and financial management of micro businesses. Not only technical skills, this training also equips participants with soft skills such as business communication skills, teamwork, and creative and innovative thinking. The results of the activity showed a significant increase in participants' understanding of the basic principles of entrepreneurship and readiness to start a business independently. The pre-test and post-test evaluations showed a spike in comprehension scores, while the business plan products developed by participants showed creativity and the use of local potential that had not been previously worked on. Some participants have even formed community-based small business groups. This training also succeeded in forming an adaptive and innovative entrepreneurial mindset and building a social network that supports business collaboration.